HUBUNGAN PENDIDIKAN KEJURUAN DENGAN PRODUKTIVITAS KERJA PERSONIL POLRES KERINCI: M. DHANY ALSUNAH, S.Pd., M.Pd - M Dhany Alsunah (LPPM STIA Nusantara Sakti, 2019)
Relationship of Vocational Education with Work Productivity of Kerinci Police Personnel. With the Problem Formulation Is There a Relationship Between Vocational Education With Work Productivity Of Kerinci Police Personnel And Some Relationships Of Vocational Education With Work Productivity Of Kerinci Police Personnel. The Following Purpose of This Research To Determine the Relationship Between Vocational Education With Work Productivity Of Kerinci Police Personnel And Some Relationships Of Vocational Education With Work Productivity Of Kerinci Police Personnel. This study uses a quantitative method in which research methods based on the philosophy of positivism are used to examine specific populations or samples. From the Research Results Using the Spearman Rank Correlation Known about Vocational Education Significantly Related to the Work Productivity of Kerinci Police Personnel. The Conclusions Of This Research Are Related To The Significant Relationship Between Vocational Education To The Work Productivity Of Kerinci Police Personnel With Values.